Management of Vaginal Prolapse in a Bitch by Conservative Approach - Nahak, Anil Kumar; Behera, Himanshu; Patra, Bijay Kumar; Pati, Prasanna; Mahapatra, Samapika (The Indian Journal of Animal Reproduction, 2024)
A 3 year old bitch presented at Veterinary Clinical Complex, OUAT, Bhubaneswar with a history of protruded doughnut shaped bright red vaginal mass was undertaken physical, cytological, ultrasonographic and hormonal examination  which confirmed vaginal prolapse in late pro-estrus stage of non pregnant bitch. Conservative approach of treatment by  repositioning and suturing along with hormone, antibiotic therapy was carried out for management.
Keywords: Doughnut; Estrus; Medroxy progesterone acetate